2023
DOI: 10.1007/s12517-023-11373-6
|View full text |Cite
|
Sign up to set email alerts
|

ANN-based estimation of pore pressure of hydrocarbon reservoirs—a case study

Abstract: In seismic methods, pore pressure is estimated by converting seismic velocity into pore pressure and calibrating it with pressure results during the well-testing program. This study has been carried out using post-stack seismic data and sonic and density log data of 6 wells in one of the fields in SW Iran. While an optimum number of attributes is selected, the General regression (GRNN) provides higher accuracy than Back Propagation (BPNN) at the initial prediction stages. However, Acoustic Impedance (AI) is th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…Machine learning is effectively used by Man et al (2021) to boost the prediction of permeability and reduces uncertainty in reservoir modeling. Recently, a variety of conventional methods and machine learning algorithms were investigated in determining hydraulic flow units (HFUs), and the performance of each method was evaluated (Fernandes et al, 2023a;Kianoush et al, 2022bKianoush et al, , 2023cKianoush et al, 2023a;Masroor et al, 2023;mohammadinia et al, 2023;Shi et al, 2023;Yu et al, 2023). Salavati et al (2023) used hydraulic flow units, multi-resolution graphbased clustering, and fuzzy c-mean clustering methods to determine rock types.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning is effectively used by Man et al (2021) to boost the prediction of permeability and reduces uncertainty in reservoir modeling. Recently, a variety of conventional methods and machine learning algorithms were investigated in determining hydraulic flow units (HFUs), and the performance of each method was evaluated (Fernandes et al, 2023a;Kianoush et al, 2022bKianoush et al, , 2023cKianoush et al, 2023a;Masroor et al, 2023;mohammadinia et al, 2023;Shi et al, 2023;Yu et al, 2023). Salavati et al (2023) used hydraulic flow units, multi-resolution graphbased clustering, and fuzzy c-mean clustering methods to determine rock types.…”
Section: Introductionmentioning
confidence: 99%
“…Compilation of core porosity and permeability are used to identify these units. Yasmaniar et al (2018) utilized Artificial Neural Network (ANN) to determine the permeability of different Rock Type Using the Hydraulic Flow Unit Concept (Ding et al, 2022;Kharrat et al, 2009;Kianoush et al, 2023c;Mahadasu and Singh, 2022;Masroor et al, 2023;Rafik and Kamel, 2017). Oliveira et al (2020) demonstrated that an inter-clustering process is recommended when selecting data points associated with representative volumes and local spots characterizing HFUs.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning is effectively used by Man et al (2021) to boost the prediction of permeability and reduces uncertainty in reservoir modeling. Recently, a variety of conventional methods and machine learning algorithms were investigated in determining hydraulic flow units (HFUs), and the performance of each method was evaluated (Fernandes et al, 2023a;Forbes Inskip et al, 2020;Kianoush et al, 2022bKianoush et al, , 2023cKianoush et al, 2023a;Masroor et al, 2023;mohammadinia et al, 2023;Shi et al, 2023;Yu et al, 2023). Salavati et al (2023) used hydraulic flow units, multi-resolution graph-based clustering, and fuzzy c-mean clustering methods to determine rock types.…”
Section: Introductionmentioning
confidence: 99%
“…Compilation of core porosity and permeability are used to identify these units. Yasmaniar et al (2018) utilized Artificial Neural Network (ANN) to determine the permeability of different Rock Type Using the Hydraulic Flow Unit Concept (Ding et al, 2022;Kharrat et al, 2009;Kianoush et al, 2023c;Mahadasu & Singh, 2022;Masroor et al, 2023;Rafik & Kamel, 2017). Oliveira et al (2020) demonstrated that an inter-clustering process is recommended when selecting data points associated with representative volumes and local spots characterizing HFUs.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning is effectively used by Man et al (2021) to boost the prediction of permeability and reduces uncertainty in reservoir modeling. Recently, a variety of conventional methods and machine learning algorithms were investigated in determining hydraulic flow units (HFUs), and the performance of each method was evaluated (Fernandes et al, 2023a;Kianoush et al, 2022bKianoush et al, , 2023cKianoush et al, 2023a;Masroor et al, 2023;mohammadinia et al, 2023;Shi et al, 2023;Yu et al, 2023). Salavati et al (2023) used hydraulic flow units, multi-resolution graphbased clustering, and fuzzy c-mean clustering methods to determine rock types.…”
Section: Introductionmentioning
confidence: 99%